The antecedence of green supply chain management and its impact on business performance in the traditional fashion industry - Hadjar, Farah Muhammad; Kusmantini, Titik; Sabihaini, Sabihaini (Asian Management and Business Review, 2023)
This study aims to identify and analyze the antecedence of GSCM and their impact on business performance in the traditional fashion industry. This study uses a quantitative method by collecting data through a survey conducted using a questionnaire. For this analysis, the object of this research is a total of 60 traditional fashion industries in Yogyakarta. The sampling method used is a census, namely surveying the population as a whole. The analysis technique used in this research is Structural Equation Modeling (SEM) using Partial Least Squares (PLS) 4.0. Based on the results of this study: supply chain connectivity has a significant positive effect on GSCM; owner commitment has a significant positive effect on GSCM; GSCM has a significant positive effect on business performance; supply chain connectivity has a significant positive effect on business performance; owner commitment has a significant positive effect on business performance; supply chain connectivity has a significant positive effect on business performance through GSCM as a mediating variable; and owner commitment has a significant positive effect on business performance through GSCM as a mediating variable. The recommendation from this study is that hopefully, in the future, more SMEs will increase owner commitment in several aspects such as developing cooperation, working together to create competitive advantage, developing vision and mission, and developing metrics to monitor business success together.